Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai pada Dinas Koperasi Kota Semarang - Alexander Nova Vernando; Muh Fajrul; Anang Tri Wahyono; Erlitawati Kaharudin (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Human Resources (HR) is one of the important factors in every existing government agency. Superior human resources are one of the main keys in determining the success and competitiveness of a government agency. This study aims to understand the influence of work motivation and work environment on employee performance. Work motivation is defined as the internal and external drives that influence employee behavior, while the work environment refers to the physical and psychological conditions of the workplace. Employee performance is measured through efficiency, effectiveness, and productivity in carrying out their duties and responsibilities. The number of samples in this study was 74 employees using saturated sampling. The results of the study show that work motivation and work environment have a significant influence on employee performance. The results of the study show that work motivation partially has a significant and positive effect on employee performance, with a calculated t of 2.532 > t table 0.678 and a significance value of 0.027 < 0.05. Work motivation positively influences employee performance because motivated employees tend to show better performance. Meanwhile, the work environment partially also has a very significant and positive influence on employee performance, with a calculated t result of 1.914 > t table 0.678 and a significant value of 0.000 < 0.05. A conducive work environment also contributes to improving employee performance. However, this study also found that work motivation and the work environment cannot function optimally without the support of management and appropriate service policies. Therefore, it is recommended for government agencies to continue implementing effective motivational strategies and creating a conducive work environment to improve employee performance.